Secagem por aspersão de nanocápsulas de núcleo lipídico contendo tretinoína: desenvolvimento e incorporação em hidrogéis - Marchiori, Marila Crivellaro Lay (2010)
The aim of this work was to study the ability of lipid-core polymeric nanocapsules to protect tretinoin against UV degradation, even after their conversion to spray-dried powders and also to evaluate the feasibility of using these spray-dried powders in the preparation of semisolid dermatological nanomedicines. Spray-dried tretinoin-loaded lipid core nanocapsules (SD-TTN-NC) were prepared using lactose as drying adjuvant. In order to study the effect of the polymeric layer, spray-dried powders were also prepared using a nanoemulsion (SD-TTN-NE). The process yields were between 30 and 40 %. SD-TTN-NE showed lower encapsulation efficiency (88.74 ± 0.65%) compared to SD-TTN-NC (94.22 ± 2.01%). After aqueous redispersion of the spray-dried powders their supernatants showed the presence of nanostructures with mean size close to the original suspension Similar photodegradation half-life times were showed for tretinoin loaded in lipid-core nanocapsules (118 ± 12 min) or in the respective spray-dried powders (118 ± 27 min). Based in our results, the powders can be suggested as intermediate products in the development of nanomedicines. Two approaches were evaluated in the development of hydrogels: a) dispersing Carbopol Ultrez 10® in an aqueous redispersion of the SD-TTN-NC (method 1) or b) by the direct incorporation of the SD-TTN-NC in a hydrogel previously formed (method 2). Hydrogels were also prepared using original nanocapsule suspensions. All semisolid formulations presented drug content close to theoretical value, adequate pH values and pseudo-plastic behavior. The parallel plate technique demonstrated that hydrogels prepared by method 1 has lower spreadability (1.61 ± 0.13 mm2.g-1) than that prepared by method 2 (2.17 ± 0.05 mm2.g-1). However, both formulations showed worst spreadability factor than hydrogels prepared from nanoparticle suspensions, indicating that the presence of lactose led to a decrease in the spreadability of the formulations. Hydrogels prepared with the spray-dried powder showed higher yield stress compared to that prepared with the nanocapsule suspensions. Regarding the consistency index, all hydrogels presented similar values, excepting the formulation prepared with blank nanocapsules. The photodegratadion profiles of hydrogels containing SD-TTN-NC were similar to hydrogel prepared with the original suspension. So, spray-dried powders were feasible materials to be use as intermediate products in the development of hydrogels intended for cutaneous application without losing their ability to increase the photostability of tretinoin.